Visible light-responsive hydrogels for cellular dynamics and spatiotemporal viscoelastic regulation - Yan Lu; Cheng Chen; Hangyu Li; Peng Zhao; Yuanfeng Zhao; Bohan Li; Wei Zhou; Gaofeng Fan; Dongshi Guan; Yijun Zheng (Nature Communications)
Abstract Viscoelastic heterogeneity of matrices plays a pivotal role in cancer cell spreading, migration, and metastasis. However, the creation of viscoelastic platforms with spatial-temporal regulation is hindered by cytotoxicity and short regulation durations. Our research presents a dual mechanism for stress relaxation regulation- both intrinsic and responsive- by incorporating Schiff base bonds and a visible light-responsive thiuram disulfide (TDS) moiety into the hydrogel. Modifying base bonds facilitates a broad spectrum of intrinsic stress relaxation times. At the same time, incorporating the visible light-responsive TDS moiety endows the hydrogel with responsive viscoelastic properties. These properties are characterized by minimal cytotoxicity, spatial-temporal controllability, dose dependency, and reversibility. Utilizing this platform, we demonstrate that ovarian cancer cells exhibit contrasting behaviors in contraction and spreading when subjected to dynamic stress relaxation changes over various time periods. Additionally, we observed a “memory effect” in the cell’s response to alterations in stress relaxation time. We can spatially direct cell migration through viscoelastic heterogeneity, achieved via photopatterning substrates and laser spots. This innovative approach provides a means to regulate the viscoelasticity of hydrogels across a wide range of timescales, thereby opening avenues for more advanced studies into how cells interpret and respond to spatiotemporal viscoelastic signals.